Advanced deep reactive‐ion etching technology for hollow microneedles for transdermal blood sampling and drug delivery. Issue 2 (1st June 2013) - Liu, Yufei; Eng, Pay F.; Guy, Owen J.; Roberts, Kerry; Ashraf, Huma; Knight, Nick
Abstract : Using an SPTS Technologies Ltd. Pegasus deep reactive‐ion etching (DRIE) system, an advanced two‐step etching process has been developed for hollow microneedles in applications of transdermal blood sampling and drug delivery. Because of the different etching requirements of both narrow deep hollow and large open cavity, hollow etch and cavity etch steps have been achieved separately. This novel two‐step etching process is assisted with a bi‐layer etching mask. Results show that the etch rate of silicon during this hollow etch step was about 7.5 µm/min and the etch rate of silicon during this cavity etch step was about 8–10 µm/min, using the coil plasma etching power between 2.0 and 2.8 kW. Especially for the microneedle bores etch, the deeper it etched, the slower the etch rate was. The microneedle bores have successfully been obtained 75–150 μm in inner diametre and 700–1000 μm long with high aspect ratio DRIE, meanwhile, the vertical sidewall structures have been achieved with the high etch load exposed area over 70% for the cavity etch step.